Panoramic image stitching - Wong, Joniece Jing Yi (2014)
Panoramic images were first created in the middle of the 19th century and it became popular in modern days. It has progressed greatly through the use of computer image processing methods to create panoramas digitally. The word ‘panorama’ comes from the Greek words pân and hòrama, which meant ‘to see everything’. [2]